Nivel de depresión según la cronicidad de la Diabetes Mellitus tipo 2 y sus comorbilidades en pacientes de las Unidades de Salud, Encarnación, Paraguay 2018 - Addis Rivarola Sosa; Marta Brizuela; Angel Rolón-Ruiz Díaz (Instituto Nacional de Salud (INS), 2019)
Introduction: Type 2 Diabetes Mellitus is a very frequent metabolic disease, being one of the main causes of mortality in our country. The integral, individual, family and community approach of Primary Health Care through the Family Health Units allows to identify symptoms of depression that may appear during the course of the disease. Objective:To determine the levels of depression according to the chronicity of Type 2 Diabetes Mellitus and its comorbidities in patients of the Health Units of the district of Encarnación in the year 2018. Methodology:Study with observational, analytical cross-sectional design on 228 patients with Type 2 Diabetes Mellitus interviewed during 2018. A validated form was applied with the Kuder-Richardson test and the Hamilton Scale for depression. The data was processed in EpiInfo v. 7. Results:Depression was detected in 66.7% (152) of the people included in the study, with mild depression being more frequent in 32.9% (75) of the cases, followed by moderate and severe depression. A statistically significant association was found between depression and years of evolution of Type 2 Diabetes Mellitus (p = 0.029), hypertension (p = 0.0024); neuropathy (p = 0.0003). Conclusion: The most frequent level of depression was mild and the presence of depression symptoms in patients with Type 2 Diabetes Mellitus was high, significantly associated with years of evolution of diabetes, hypertension and neuropathy.